2013
DOI: 10.1002/bjs.9177
|View full text |Cite
|
Sign up to set email alerts
|

Predicting aortic complications after endovascular aneurysm repair

Abstract: The risk score uses commonly available morphological data to stratify the rate of complications after EVAR. The proposals for rationalized surveillance could provide clinical and economic benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Results were compared with current clinical method such as; SGVI (St George Vascular Institute), which showed that the proposed method has superior performance. The seven features ANN of the proposed method have greater predictive ability in classifying low and high risk patients than the SGVI score [ 91 ]. Concordance index, estimated AUC, and p -value of the predictive model using the selected features show good clinical sense.…”
Section: Discussionmentioning
confidence: 99%
“…Results were compared with current clinical method such as; SGVI (St George Vascular Institute), which showed that the proposed method has superior performance. The seven features ANN of the proposed method have greater predictive ability in classifying low and high risk patients than the SGVI score [ 91 ]. Concordance index, estimated AUC, and p -value of the predictive model using the selected features show good clinical sense.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing aneurysm diameter also increases the risk of complications and reinterventions after elective endovascular repair. 17 , 18 Although the anatomical assessment of suitability for EVAR is defined primarily by neck length, diameter and angle, and access artery characteristics, it was neck length that was the most common factor precluding EVAR (<10 mm in 23%, <15 mm in 33%). For each increase of 15 mm in neck length, 30-day mortality decreased by a factor of ∼20%, with a similar effect on 24 h mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This would be consistent with the relevance of these two parameters in predicting complications after elective aneurysm repair. 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…The risk of endograft-related complications is heterogeneous[ 8 ] and a minority of patients fall within a high-risk cohort[ 8 ]. Endograft complications and reinterventions are related to pre-operative aneurysm morphology[ 17 , 18 ], but current statistical models have proved insufficiently discriminatory for clinical use. Furthermore, existing risk models have not proved capable of predicting limb complications such as stenosis or occlusion, which remain a source of morbidity.…”
Section: Introductionmentioning
confidence: 99%